2001
DOI: 10.1021/ac001200w
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry for On-Line Monitoring of Perfluoro Compounds Using Li+ Ion Attachment Techniques

Abstract: Ion attachment mass spectrometry is being developed for continuous measurement of perfluoro compounds (PFCs) found in the atmosphere as a result of semiconductor manufacturing processes. Studies were made on 5 greenhouse gases, CF4, CHF3, C2F6, SF6, and c-C4F8, to develop improved methods for PFC analysis, particularly at levels found in the atmosphere (the parts-per-billion concentration range). The results demonstrate the feasibility of performing real-time measurements of the trace amounts of PFCs encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…It is fragment-free in most cases and allows us to observe even neutral saturated straight-chain PFCs as their Li + adducts in mass spectrometry. 6,7 Using this technique, we have recently found that various neutral molecules, as well as positive ions with mass numbers as high as 400 amu (where the maximum mass number is determined by the limitations of our mass spectrometer), are present in the downstream region of Ar/CF 4 plasmas. 8 In addition, we have clarified the growth mechanism of their high-mass positive ions.…”
Section: Introductionmentioning
confidence: 99%
“…It is fragment-free in most cases and allows us to observe even neutral saturated straight-chain PFCs as their Li + adducts in mass spectrometry. 6,7 Using this technique, we have recently found that various neutral molecules, as well as positive ions with mass numbers as high as 400 amu (where the maximum mass number is determined by the limitations of our mass spectrometer), are present in the downstream region of Ar/CF 4 plasmas. 8 In addition, we have clarified the growth mechanism of their high-mass positive ions.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption does not significantly affect the calculation of the flow rate according to the following Eq. (9)- (15).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the scrubber efficiency is obtained by on-line based on Fourier Transform Infrared Spectroscopy (FTIR) 13,14 or real time Quadrupole Mass Spectrometry (QMS) method. 15,16 Under these methods, the PFC amount has to be calculated considering the flow rate, pressure, and temperature at inlet and outlet of the scrubber. 13,17 Here, we suggest a reliable method to obtain the efficiencies of various scrubbers in accordance with the guidelines by the IPCC.…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus was essentially the same as that used previously in a number of other studies of the free radicals formed in MW discharge plasmas [ Fujii , 2000; Selvin and Fujii , 2001; Fujii et al , 2001]. Briefly the apparatus consists of a 15‐cm flow tube, combined with a Li + ion attachment mass spectrometer (Anelva Corp., Tokyo, Japan), and the products (M) were detected and assigned as their lithium adducts (M + Li) + .…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The recently developed Li + ion attachment mass spectrometry (Li + MS) technique provides mass spectra of quasi‐molecular ions formed by lithium ion attachment to chemical species under high pressure [ Fujii , 2000; Selvin and Fujii , 2001; Fujii et al , 2001]. Results are obtained in the form of mass spectrometric traces of Li + adducts.…”
Section: Introductionmentioning
confidence: 99%